A Study On Emotional Branding vs. Rational Branding and Their Impact on Customer Loyalty - Ayush Rajput; Jignesh Vidani (Journal of Advanced Research in Economics and Business Management, 2025)
Branding strategies are crucial for influencing consumer loyalty and behaviour in today’s fiercely competitive and emotionally charged industry. By contrasting the impacts of rational and emotional branding on customer loyalty, this study offers valuable new insights into how businesses can foster long-lasting relationships with their clients. Emotional branding aims to establish relationships through narrative, personal beliefs, emotional resonance, and shared experiences. It aims to create a sense of identification and belonging by appealing to the psychological and emotional aspects of consumer decision-making. On the other hand, clear and practical factors like features, performance, cost, and product quality are key to rational branding. Customers who value saving money and making informed choices usually focus on these things. While rational branding helps attract new customers, emotional branding has been shown to be better at keeping current customers and encouraging repeat business. By appealing to customers’ feelings in ways that go beyond logic, brands can build real connection, trust, and lasting loyalty. This distinction between rational and emotional branding forms the foundation for analysing consumer responses. This study uses a structured questionnaire to gather data on consumer preferences and opinions from a large sample of participants. The study looks into how consumers respond to emotional versus rational branding.